Multiculturalism in the Light of Rawls' Theory of Justice - A A Surkov (RUDN Journal of Philosophy, 2012)
This article is devoted to analysis of the phenomenon of multiculturalism in the modern society through methodology offered by John Rawls in the Theory of Justice. Due to theoretical model of social contact we can draw conclusions on multiculturalism problems within conditions of democracy. Basic alternatives created by opponents of the theory of multiculturalism are also discussed.